The productivity puzzle in business services - Alexander Kritikos; Alexander Schiersch; Caroline Stiel (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
In Germany, the productivity of professional services, a sector dominated by micro and small firms, declined by 40 percent between 1995 and 2014. This productivity decline also holds true for professional services in other European countries. Using a German firm-level dataset of 700,000 observations between 2003 and 2017, we analyze this largely uncovered phenomenon among professional services, the 4th largest sector in the EU15 business economy, which provide important intermediate services for the rest of the economy. We show that changes in the value chain explain about half of the decline and the increase in part-time employment is a further minor part of the decline. In contrast to expectations, the entry of micro and small firms, despite their lower productivity levels, is not responsible for the decline. We also cannot confirm the conjecture that weakening competition allows unproductive firms to remain in the market.
Keywords: L84; O47; D24; L11; 330; business services; labor productivity; productivity slowdown